Cochrane Skin Group's Global Social Media Reach: Content Analysis of Facebook, Instagram, and Twitter Posts - Areebah Ahmad; Lina Alhanshali; Itisha S Jefferson; Robert Dellavalle (JMIR Publications, 2022)
BackgroundResearchers in all medical specialties increasingly use social media to educate the public, share new publications with peers, and diversify their audiences. ObjectiveGiven Cochrane Skin Group's expanded use of social media in the past years, we aimed to characterize Cochrane Skin Group's international social media audience and identify themes that result in increased content engagement. MethodsCochrane Skin Group's Facebook, Instagram, and Twitter analytics data were extracted for follower demographics and the most viewed posts within a 3-year span (June 2019 to June 2022). ResultsOverall, Cochrane Skin Group had the highest number of followers on Facebook (n=1037). The number of Instagram and Twitter followers reached 214 and 352, respectively. The greatest numbers of Facebook followers were from Brazil, Egypt, and India, with 271, 299, and 463 followers, respectively. Facebook's most viewed post about Cochrane Skin Group's annual meeting received 1041 views. The top post on Instagram, which introduced Cochrane Skin Group's social media editors, received 2522 views. ConclusionsEach of the social media platforms used by Cochrane Skin Group reached varying audiences all over the world. Across social media platforms, posts regarding Cochrane Skin Group meetings, members, and professional opportunities received the most views. Overall, Cochrane Skin Group's multiplatform social media approach will continue to grow an international audience, connecting people interested in skin disease.